Colistin Heteroresistance among Extended Spectrum β-lactamases-Producing Klebsiella pneumoniae - Felipe Morales-León; Celia A. Lima; Gerardo González-Rocha; Andrés Opazo-Capurro; Helia Bello-Toledo (Microorganisms, 2020)
Colistin-heteroresistant (CST-HR) Enterobacterales isolates have been identified recently, challenging the clinical laboratories since routine susceptibility tests fail to detect this phenotype. In this work we describe the first CST-HR phenotype in extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae isolates in South America. Additionally, we determine the genomic mechanisms of colistin heteroresistance in these strains. The CST-HR phenotype was analyzed by the population analysis profile (PAP) method, and mutations associated with this phenotype were determined by whole-genome sequencing (WGS) and the local BLAST+ DB tool. As a result, 8/60 isolates were classified as CST-HR according to the PAP method. From WGS, we determined that the CST-HR isolates belong to three different Sequence Types (STs) and four K-loci: ST11 (KL15 and KL81), ST25 (KL2), and ST1161 (KL19). We identified diverse mutations in the two-component regulatory systems PmrAB and PhoPQ, as well as a disruption of the mgrB global regulator mediated by IS1-like and IS-5-like elements, which could confer resistance to CST in CST-HR and ESBL-producing isolates. These are the first descriptions in Chile of CST-HR in ESBL-producing K. pneumoniae isolates. The emergence of these isolates could have a major impact on the effectiveness of colistin as a “last resort” against these isolates, thus jeopardizing current antibiotic alternatives; therefore, it is important to consider the epidemiology of the CST-HR phenotype.